Multiple nucleolus organizer regions in Leptodactylus mystacinus (Amphibia, Anura) and comments on its systematic position in the L fuscus group based on cytogenetic and molecular analyses - Zampieri Silva, Ana Paula; Baptista Haddad, Celio Fernando; Galassi, Guilherme Guidolin; Kasahara, Sanae (Springer, 2006)
Specimens of Leptodactylus mystacinus from Brazil were karyotyped with conventional and differential staining. The 2n = 22 karyotype is similar to that found for the majority of the Leptodactylus, the karyotypic conservatism also confirmed by the similarity of the replication banding patterns with those previously described. L. mystacinus has a small amount of C-banded heterochromatin, located mainly at the centromeres, although telomeric or interstitial bands have also been noticed. With DA/CMA(3) some chromosome regions showed slightly bright fluorescence, and with DA/DAPI, no particular AT-rich repetitive region was observed. Silver staining showed an extensive inter- and intraindividual variation in the number and position of Ag-positive regions, in 1p, 4p, 8p, 8q, and 11p. Nevertheless, FISH using rDNA probes confirmed only the signals on the short arms of chromosomes 4 and 8 as true NORs. The remaining silver stained regions are probably due to the heterochromatin with some affinity to the Ag-staining. Phylogenetic analysis based on partial cytochrome b sequence revealed that L. mystacinus forms a basal branch, so that the presence of multiple NORs in pairs 4 and 8 in this species indicates an autapomorphy.
Keywords: Ag-NORs; BrdU incorporation; C-banding; FISH; fluorochrome staining